The role of blockchain to reduce the dissemination of fake news on social media and messaging platforms - Aranda-Tyrankiewicz, Marta (Cybersecurity in the age of smart societies, 2023)
The world is progressing further into the digital era, and as a result, more and more people are getting their initial information from online news portals and social media platforms. The dependence on sources of information that are becoming murkier raises the likelihood of being deceived and the possibility of misguided agendas. When it comes to verifying articles, traditional news outlets adhere to stringent norms of practice. In contrast, people nowadays are able to publish news items on social media and unverified sites without having to provide evidence that they are true. Because there are now no indicators on the Internet that can be used to gauge the veracity of such news pieces, an innovative strategy that makes use of technology is required in order to evaluate the realness quotient of unconfirmed news items. This paper proposes a dynamic model with a secure voting mechanism that allows news reviewers to submit news input. A probabilistic mathematical model is utilised to estimate the news item’s veracity based on the feedback obtained from the news reviewers. In order to guarantee that the information being spread is accurate, the concept, which is based on blockchain technology, will be presented.